Physical Therapy at the postoperative of hip endoprosthesis for osteosarcoma: a case report - Venâncio, Raysa Silva; Martins, Tamiris Beppler; Santos, Keyla Mara dos; Palandi, Juliete; Sinhorim, Larissa; Santos, Gilmar Moraes (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Osteosarcoma is the most common malignancy among musculoskeletal tumors. It can be treated for preservation member or amputation. The cases treated for preservation member have improved functionality and quality of life, however, patients with oncologic diseases exhibit symptoms of anxiety and depression. Objective: The aim of this study is to describe the role of physiotherapy in the hip endoprosthesis after surgery for osteosarcoma of a patient treated at the Clinic Physiotherapy School of the University of the State of Santa Catarina (CEFID / UDESC) and verify their quality of life, functionality and symptoms of anxiety and depression. Methods: A descriptive study through case report. The subject was assessed before and after 10 sessions of physiotherapy on the quality of life, functionality and symptoms of anxiety and depression using a standardized assessment form, the Quality of Life Assessment Questionnaire (WHOQOL-BREF), the system Functional assessment (Musculoskeletal Tumor Society Rating Scale - MSTS); of Lower Limb Function Scale (EFMI) and the Hospital Anxiety and Depression Scale (Hospital Anxiety and Depression Scale - HADS); Results and Conclusions: Physical therapy treatment proposed to the patient allowed the increase of muscle strength; increased muscle tropism; improved member functionality (65% of EFMI); possible reduction of anxiety or depressive symptoms in HADS; presenting score (67.31%) of the WHOQOL-BREF and (56%) in MSTS. Thus, based on the functional, emotional and psychological outcomes, the proposed physical therapy had a positive influence on a patient’s quality of life osteosarcoma at the proximal end of the left femur, underwent resection and reconstruction member with endoprosthesis.